Common syntactic errors among Arab tweeters on twitter and their impact on understanding - Alanazi, Nujud Ismail R. (2020)
Arabic Language is exposed to many manifestations of negative language, such as the phenomenon of common syntactic errors on social media, especially "Twitter", as the frequent occurrence of syntactic errors among individuals makes people accept these errors and consider them to be right. The purpose of this study was to monitor syntactic errors of Arab Tweeters. Therefore, this study aimed to analyze general syntactic errors, and thus determine the prevalence of these errors with simple statistical indicators, the study also sought to verify the extent of the errors in understanding the tweets. In order to achieve these goals, researcher used qualitative research methods, and data was collected from tweets using standard Arabic only to avoid using Arabic dialects. Samples were also collected randomly (not selectively), but systematically of scientific importance, by choosing tweets regardless of the user’s own intentions. The study sample consisted of 500 syntactic errors between 2016 to 2018. The data were analyzed qualitatively and descriptively, applying the theory of error analysis in the Arabic tradition. Then, determining the percentage of prevalence among them with statistical and descriptive indications by the statistical program. The study reached several results, the most important of which were: The phenomenon of syntactic errors was common among the eloquent writings of Arabic Tweeters in all chapters of grammar (name, verb, and letter) with different proportions and qualities. The errors in the name section became very common, and the issue of settling on tweets arose in Twitter, as they inhabited the raised, deserved, and drawn name, and the phenomenon of raising and dragging the trashed monument from the name spread other than errors in composing sentences. This is due to the branching of the rules in the name, and the nature of the continuous change in its cases. As for the matter of action, errors in the present tense were common compared to the past and the command. The dominant feature of the Arab tweets was the raising and erection of the present tense that it is right to say. As for the letter section, it has two issues: exchanging prepositions in their use, and combining conjunctions. After examining and following up on the reactions of Twitter users, the study revealed that syntactic errors do not affect the understanding of the text among readers, as the interaction between the tweets was clear, which confirms the absence of a communication understanding gap between them, whether it is the frequent responses and comments on the wrong tweet, or by placing an admiration signal, or post the tweet and resend them. These errors will certainly affect the Arabic language in the future, as it may affect accuracy, and impede the development and progress of the Arabic language itself. This will also increase the knowledge gap between Arabic language and native speakers and will undermine the methods and cause them to fall behind.